ESTIMATION OF RANK BASED QUOTIENT (RBQ) FOR SWOT ON PRACTICING SOYBEAN PRODUCTION TECHNOLOGIES IN THE NORTHERN TELANGANA ZONE - REDDY, K. MADAN MOHAN; MOHAN REDDY, M. JAGAN (The Bioscan, 2016)
The present study was conducted on soybean production to estimate theRank Based Quotient (RBQ) for SWOT on practicing soybean production technologies in Adilabad, Nizamabad and Karimnagar districts of Northern Telangana zone of Telangana state. The major RBQ-strengths are less number of irrigations required during the crop period, JS335 is high yielding variety and fixation of the atmospheric nitrogen in to the soil by the soybean crop due to its leguminous nature. The major RBQ-weaknesses JS335 is a semi-dwarf variety and low seed viability, lack of suitable high yielding varieties to the zone other than JS335. Low incidence of pest and diseases in line sowing followed by low cost of plant protection, harvest indices are easy to understand and practice are top three RBQ-opportunities in practicing soybean production technologies. The major RBQ-threats are yield reduction in rabi season followed by more soil erosion in red soils due to heavy rains, lack of varieties suitable for rabi season.